The International Consensus on ANA Patterns (ICAP) in 2021—The 6th Workshop and Current Perspectives. (5th January 2022) - Chan, Edward K L; von Mühlen, Carlos A; Fritzler, Marvin J; Damoiseaux, Jan; Infantino, Maria; Klotz, Werner; Satoh, Minoru; Musset, Lucile; García-De La Torre, Ignacio; Carballo, Orlando Gabriel; Herold, Manfred; de Melo Cruvinel, Wilson; et al.
Abstract: The establishment of the International Consensus on ANA Patterns (ICAP) in 2014–2015 was welcomed by members of the medical community as a significant improvement in guiding harmonization of ANA test interpretation and reporting. In the subsequent years, several itinerant meetings and continuous interaction with the community contributed to disseminate the ICAP harmonization on the immunofluorescence patterns observed in the indirect immunofluorescence assay on HEp-2 cells (HEp-2 IFA) and to promote progressive improvement in the classification of HEp-2 IFA patterns. The 6th ICAP Workshop was held in person on September 6, 2021 as a satellite meeting of the 15th Dresden Symposium on Autoantibodies. This article summarizes the major discussions at the meeting as well as outlining the current plans for the ICAP committee.